Cognitive Levels and Material Quality of Reading Comprehension Questions in the Grade XI English for Change Textbook - Zahra, Intan Karima; Abdulrahman, Tryanti; Putri, Hana Amanda (Journal of Learning Improvement and Lesson Study, 2026)
This study aims to analyze the cognitive levels and material quality of reading comprehension questions in the English for Change Grade XI textbook. In response to concerns that English textbooks tend to emphasize lower-order thinking skills (LOTS), this study examines the extent to which the questions support students’ cognitive development and reflect effective principles of language learning materials. A qualitative content analysis design was employed to analyze 30 reading comprehension questions from five chapters. Cognitive levels were classified using Bloom’s Revised Taxonomy, while material quality was evaluated based on Tomlinson’s principles of language learning materials development. The integration of these frameworks offers a multidimensional evaluation of reading comprehension questions, considering both cognitive demands and pedagogical quality. The findings show that most questions target Understanding (53.3%) and Remembering (33.3%), with minimal representation of higher-order thinking skills (HOTS). Cognitive Engagement was dominant (94%), whereas Communicative Purpose, Self-Investment, and Learner Relevance received limited attention. The study highlights reading comprehension questions as cognitive and pedagogical tools that support meaningful learning and higher-order thinking development in EFL contexts